Berbagai Pendekatan Komunikasi Lintas Budaya Bagi Masyarakat Dayak - Harming Harming (Sekolah Tinggi Teologi Tenggarong, 2021)
This paper discusses various approaches to cross-cultural communication. This study focuses on Christian communication where this communication model is slightly different from communication in general. Christian communication focuses on discussion of gospel truths conveyed across cultures. In communicating, obstacles often occur due to differences in characteristics, language, perceptions, physicality and culture. If these obstacles are not managed properly, they will cause conflict and have an impact on a person's life and society. The method I use is library research, which is to express ideas and ideas by analyzing various library sources. The analysis process is carried out by means of literature study, namely collecting sources in the form of journals related to cross-cultural communication and books on communication so that an overview is found related to the topics discussed. The results found are various cross-cultural communication approaches that can be used, including the Interpersonal communication approach; approach theory, Contextual Theory.